166k views
2 votes
Solve using the substitution method ​

Solve using the substitution method ​-example-1
User Parfilko
by
5.6k points

2 Answers

6 votes

Answer:

x=4.5, y=0

Explanation:

y = 2x-9

2x + 3y= -2

2x + 3(2x-9) =9

2x + 6x - 27 =9

8x - 27 =9

8x = 36

x = 4.5

y =2x-9

y =2(4.5)-9

y =9-9

y =0

User Thelovekesh
by
4.7k points
1 vote
1) y = 2x - 9. 2) 2x + 3(2x - 9) = -2. 3) 2x + 6x - 27 = -2. 4) 8x = 25. 5) x = 25/8. 6) 2(25/8) + 2 = -3y. 7) 8.25 = -3y. 8) -2.75 = y. Answer: x = 25/8, y = 11/4
User Tony Basallo
by
6.1k points